2011
DOI: 10.1002/adma.201102036
|View full text |Cite
|
Sign up to set email alerts
|

Interphases in Graphene Polymer‐based Nanocomposites: Achievements and Challenges

Abstract: Graphene constitutes a two dimensional sp2 hybridized carbon material with outstanding electrical and mechanical properties. To date, novel methods for producing large quantities of graphene and its derivatives (doped or functionalized graphenes, nanoribbons and nanoplatelets) are emerging, and research dedicated to the fabrication of polymer nanocomposites using graphenes has started. In this Research News, we summarize the synthesis and properties of graphene and its derivatives, and provide an overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(173 citation statements)
references
References 87 publications
(80 reference statements)
1
167
0
2
Order By: Relevance
“…29,204 iii) The graphene sheets act as nano-fillers, incorporated in the continuous matrix of the second component. 205 In type II composites, both HRG sheets and the second component act as continuous phases. An example could be graphene-based composite films fabricated via layerby-layer self-assembly of the individual components.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…29,204 iii) The graphene sheets act as nano-fillers, incorporated in the continuous matrix of the second component. 205 In type II composites, both HRG sheets and the second component act as continuous phases. An example could be graphene-based composite films fabricated via layerby-layer self-assembly of the individual components.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Additionally, the porosity is another important influential factor and two kinds of porosity is commonly observed: round porosity which can be because of fluids and air entrapment as fluids exert equal pressure in all sides, and irregular porosity which can be because of reinforcement bridging and relative movement of reinforcement and matrix [211]. One of the factors that dictates the interfacial interactions is the interphase and the properties of GBPNCs are significantly influenced by interphase properties [212]. Another factor that is not an integral part of microstructure but can significantly influence the microstructure is thermal fluctuation [213].…”
Section: Overall Microstructurementioning
confidence: 99%
“…Los mecanismos usados para sintetizar CNTs y grafenos juegan un papel importante en la estructura de estas CNPs y por tanto, en sus características y posteriores aplicaciones. [15,21] Las espumas poliméricas, en particular las espumas de PU, presentan una gran variedad de aplicaciones en diversas áreas debido a que se pueden formular "a medida" para satisfacer necesidades específicas en función de su naturaleza, flexible o rígida. [11,22] Actualmente, las espumas de nanocompuestos poliméricos están recibiendo una creciente atención ya que combinan la tecnología de las espumas con las propiedades de las nanopartículas, generando materiales ligeros y multifuncionales con interesantes aplicaciones.…”
Section: Motivaciónunclassified
“…fullerenes (0D), nanotubes (1D) and graphite (3D). [21,89] The outstanding properties of graphenes (Table 2.4), such as high thermal conductivity [79] and high electron mobility [89], large specific surface area [86] and gas impermeability [90], make them promising reinforcing particles for advanced composite systems. Lee et al [91] have reported a Young's modulus of ~1 TPa and an intrinsic strength of 130 GPa, being graphene the strongest material at the moment.…”
Section: Graphenementioning
confidence: 99%
See 1 more Smart Citation